Quadratic equations, Algebra

if the roots of a quadratic equation are (-2+sqrt 6) and (-2-sqrt 6), what is the equation in ax^2+bx+c=0 form?
Posted Date: 11/20/2012 4:37:50 PM | Location :

Related Discussions:- Quadratic equations, Assignment Help, Ask Question on Quadratic equations, Get Answer, Expert's Help, Quadratic equations Discussions

Write discussion on Quadratic equations
Your posts are moderated
Related Questions
Solve the system algebraically. x - 2y - 3z = negative-1 2x + y + z = 6 x + 3y - 2z = negative13

The United States is becoming more health conscious, and as a result,the problem of obesity has gotten more attention.The Body Mass Index (BMI), relates a person’s height and weigh

9x^4-x^2=0 step by step

How to do x+y+z?

??2+??2+16??-18??+145=25 Standard form (x-h)^2 +(y-k)^2 k (x^2+16x+64)^2+(y^2-18y+81)^2=25 (x+8)^2+(y-9)^2=120 (h,k)=(8,-9) R=5 Intercepts

In the earlier section we looked at using factoring & the square root property to solve out quadratic equations. The problem is that both of these methods will not always work. Not

Example : Sketch the graph of hyperbolas.                                  ( x - 3) 2 /25 - ( y + 1) 2 /49 =1 Solution Now, notice that the y term contain the minus sig